Partnership to Strengthen Leadership Capacity of Women in Agriculture and Climate Research in Africa - Ganyo, Komla Kyky; Kpadonou, Gbedehoue Esaïe; Maiga, Mariame; Huyer, Sophia; Gondwe, Therese; Segnon, Alcade C.; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Women are less represented in agricultural research and development sector representing only 25% of agricultural scientists in Africa in the last decade, and a much lower proportion of decision makers on agriculture and climate change at institutional, national, and global levels. Research activities on climate change and outputs must be inclusive, gender-oriented and promote gender equity to enable women scientists to make a greater contribution and be represented at all levels. CORAF, together with Alliance Bioversity International and CIAT (ABC) and its partners (research centres, universities, and regional coordination institute) across Africa, and through AICCRA project, capacitated women scientists from Africa in Leadership in Agriculture and Climate research. Leveraging on CORAF-ABC collaboration, CORAF plan to extend the women leadership training to other female scientists in WASCAL, and in research institutes across the continent, including CORAF region, CCARDESA region, AFAAS region, ASARECA region.